The dynamics of Sunni-Shia integration in Indonesia: a structural-functional perspective - Zulkifli, Zulkifli (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2023)
Much research has been conducted on Sunni-Shia conflicts within the Muslim world. However, there is still limited research on integrating these two denominations. Conflict and integration, in theory, represent two distinct aspects of the same issue. This study aims to elucidate the process of Sunni-Shia integration in Indonesia and the factors contributing to it, employing a structural-functionalist perspective. Additionally, it seeks to assess the potential for such integration. Through intensive library research on offline and online sources, the article uncovers three forms of Sunni-Shia integration: peaceful coexistence, accommodation, and cooperation. These outcomes stem from six interrelated factors: inclusive theology, the role of moderate actors, collective ritual practice, ‘Alid piety, friendship and kinship, and social activity. These factors play important roles in shaping the prospects of Sunni-Shia integration in Indonesia. While the inclusive theology, as the first factor, is normative and may produce normative integration aligned with the prevailing norms, the others are more functional and may elicit functional integration emerging from the functions in the society.